Eros and education - John Crutchfield (SCENARIO: Journal for Performative Teaching, Learning, Research)
This essay explores the – admittedly taboo – theme of eros as it relates to education. While eros is generally understood today in the restricted sense of sexual desire (hence the taboo), there are good reasons to expand the concept to include the full range of embodied human experiences of attraction or sensuous affinity. Such experiences are not merely physiological, but also infused with emotion and imagination, and they constitute an indelible aspect of presence. While traditional education aims more or less explicitly at suppressing the erotic dimension of presence, performative approaches – precisely because they are rooted in the body – in effect open this dimension and make it available as an area of experience, a source of knowledge, and a motivation for learning. But this introduces an element of unpredictability, even volatility; and given the complex and often unconscious movement of eros, we are never far from the zones of social taboo and therefore of ethical concern. Proponents of a performative teaching and learning culture must therefore give careful thought to the question of how to approach the erotic aspect of presence honestly, ethically, and in ways that not only promote learning but also foster self-esteem and respect.